(untitled) (IPS Journal of Nutrition and Food Science, 2025)
Abstract This review explores the impact of various cooking methods and rice varieties on the nutritional value of rice, a staple food for millions worldwide. It aims to highlight the nutritional differences between rice varieties, such as white, brown, black, red, and parboiled rice, and how these differences influence health outcomes. Additionally, the review examines common cooking methods, including boiling, steaming, pressure cooking, microwaving, fermentation, and soaking, and their effects on the retention or loss of nutrients. Key findings suggest that rice varieties differ significantly in their nutritional composition, with brown and black rice, for example, offering more fiber, antioxidants, and essential vitamins compared to white rice. Cooking methods, too, vary in their impact on the preservation of nutrients; steaming and pressure cooking are generally more effective at retaining nutritional value than boiling. The interaction between rice variety and cooking method is crucial, as some methods help preserve essential vitamins and minerals, while others can lead to significant nutrient loss. This review provides insights into optimizing rice preparation for better nutritional outcomes, guiding consumers toward healthier dietary choices.